รูปแบบการอนุรักษ์วัฒนธรรมการแสดงท้องถิ่นชุมชนมอญ เกาะเกร็ด จังหวัดนนทบุรี - นิยมทัศน์, บุญศิริ; แสงเงิน, สุพจน์; สุรัสวดี, ฉันทนา; วรรณะลี, ชนัย (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2015)
การวิจัยครั้งนี้ มีวัตถุประสงค์เพื่อ 1) ศึกษาบริบทศึกษาบริบทวัฒนธรรมการแสดง 2) ศึกษารูปแบบ วัฒนธรรมการแสดง 3) พัฒนารูปแบบการอนุรักษ์วัฒนธรรมการแสดง 4) ประเมินรูปแบบการอนุรักษ์ วัฒนธรรมการแสดง ประชากรที่ใช้ในการเก็บข้อมูล คือ ชาวบ้านในชุมชนมอญ เกาะเกร็ด 3 หมู่บ้าน ได้แก่ บ้านลัดเกร็ด บ้านเสาธงทอง และบ้านโอ่งอ่าง จำนวน 40 คน เครื่องมือที่ใช้ในการวิจัย แบบสัมภาษณ์ แบบสอบถาม ตรวจสอบข้อมูลแบบสามเส้า และวิเคราะห์ข้อมูลโดยค่าสถิติ ร้อยละ และการวิเคราะห์เนื้อหา ผลการวิจัย พบว่า 1) การแสดงท้องถิ่นมี 6 ชุด ได้แก่ รำมอญ 12 เพลง เพลงเจ้าขาว ระบำบ้านไกล การละเล่นสะบ้า การละเล่นทะแยมอญ และรำเจ้าพ่อหนุ่ม 2) รูปแบบการแสดงแต่ละประเภทประกอบด้วย การร้อง การรำ และการเล่นในเทศกาล พิธีการที่แตกต่างกัน 3) ผลการพัฒนารูปแบบการอนุรักษ์วัฒนธรรม การแสดงท้องถิ่น โดยจัดกระบวนการฝึกหัดกำหนดเป็น 3 ขั้น ได้แก่ ขั้นพื้นฐาน ขั้นมาตรฐาน และขั้นเบ็ดเตล็ด 4) ผลการประเมิน โดยจัดอบรมเชิงปฏิบัติการทดลอง พบว่า เห็นด้วยกับรูปแบบการอนุรักษ์วัฒนธรรมการ แสดงท้องถิ่นร้อยละ 79.66 The Model of Local Cultural Performance of Mon Community in KohkredNonthaburi Province The research aimed to 1) study the context of Mon local cultural performance 2) study the model of local cultural performance of Mon community 3) develop the model of Mon’s local cultural performance conservation and 4) evaluate the models of local cultural performance of Mon community in KohKred, Nonthaburi Province. The population of this research was 40 people of the 3 villages in Kohkred i.e. ; Ban Lad Kred, Ban Sao Tong Thong and Ban Ong - Ana. The research instruments ; was personal interview questionnaire. The data was analyzed by the statistics percentage value, and the content analysis. The results were as follows : 1) there were 6 local performances consisting of Mon Dance, Pleng Chao Khaw, Rabam Ban Klai, Sa Bah, Ta Yae Mon and Ram Choa Ponum. 2) The model of each performance consisted of the background, and the elements of show procedure. 3) The development of model conservation was divided into 3 levels; the basic level, standard level, and the miscellaneous level. 4) The evaluation of the model showed that the model of local cultural performance conservation was effective with 79.66%.